Predictors of engagement with peer support: analysis of data from a randomised controlled trial of one-to-one peer support for discharge from inpatient psychiatric care. (June 2023) - White, Sarah; Bhattacharya, Rahul; Bremner, Stephen; Faulkner, Alison; Foster, Rhiannon; Gibson, Sarah; Goldsmith, Lucy; Harnett, Daniella; Lucock, Mike; Patel, Akshaykumar; Priebe, Stefan; Repper, Julie; et al.
Background: A range of evidence for the effectiveness of one-to-one peer support in mental health services is emerging. Levels of engagement with peer support vary with limited studies showing few individual participant characteristics predicting engagement. Implementation factors that might predict engagement have not been considered. Methods: Data were analysed from the intervention arm of the ENRICH trial of one-to-one peer support for discharge from acute psychiatric inpatient care. Two outcomes were considered: (1) a measure of 'engaged with peer worker'; (2) number of face-to-face contacts with peer worker post-discharge. Two sets of independent variables were analysed against each outcome: (1) pre-randomisation participant characteristics; (2) implementation factors measured pre-discharge. Analyses used logistic and zero-inflated negative binomial regression models according to outcome structure. Results: Data were analysed for 265 participants randomised to peer support who had a known peer worker. Non-heterosexual participants had increased odds of engaging with peer support compared to heterosexual participants, OR = 4.38 (95% CI: 1.13, 16.9, p = .032). Longer duration of first contact with peer worker ( OR = 1.03, 95% CI: 1.00, 1.04, p < .001) and more relationship building activities in the first contact ( OR = 1.4, 95% CI: 1.13, 1.85, p = .004) were associated with greater odds of engaging with peer support. Analysis of number of contacts post-discharge showed consistent findings. Conclusions: Implementation of peer support should include a focus on relationship building in the first session of peer support. The potential for peer support to break down barriers to accessing mental health services experienced by people from marginalised communities warrants further investigation.